4x-13-6x+4=3-8x-8+2x

Simple and best practice solution for 4x-13-6x+4=3-8x-8+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-13-6x+4=3-8x-8+2x equation:


Simplifying
4x + -13 + -6x + 4 = 3 + -8x + -8 + 2x

Reorder the terms:
-13 + 4 + 4x + -6x = 3 + -8x + -8 + 2x

Combine like terms: -13 + 4 = -9
-9 + 4x + -6x = 3 + -8x + -8 + 2x

Combine like terms: 4x + -6x = -2x
-9 + -2x = 3 + -8x + -8 + 2x

Reorder the terms:
-9 + -2x = 3 + -8 + -8x + 2x

Combine like terms: 3 + -8 = -5
-9 + -2x = -5 + -8x + 2x

Combine like terms: -8x + 2x = -6x
-9 + -2x = -5 + -6x

Solving
-9 + -2x = -5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-9 + -2x + 6x = -5 + -6x + 6x

Combine like terms: -2x + 6x = 4x
-9 + 4x = -5 + -6x + 6x

Combine like terms: -6x + 6x = 0
-9 + 4x = -5 + 0
-9 + 4x = -5

Add '9' to each side of the equation.
-9 + 9 + 4x = -5 + 9

Combine like terms: -9 + 9 = 0
0 + 4x = -5 + 9
4x = -5 + 9

Combine like terms: -5 + 9 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| 60=-.16x+68.67 | | 5(-6+3x)=-12 | | (3/7x)-5/x=3 | | -1/3/2 | | 5(-6+3x)=-30 | | 79=kji | | 2-I=-42 | | x/(x+5)=10 | | 5(3x+2)=115 | | 1/7(x+21)=6 | | -7x+10=-3x-22 | | x^3-16x^2+20x+400=0 | | 3x(x)+8x=5x-4x(x) | | 2x+2=-22+5x | | (3w-1/2)=(6w-2/7)+3 | | -56-7x=19+8x | | z=14x+5y | | 7x-4=x+56 | | (11.2)2-(0.375/3) | | ((6t)^2+9)^1/2 | | 5x(x)=10x | | (.0105)(.1417)= | | -243=-90(10+x) | | p=m(1-DT) | | 120=-12(x-5) | | 7(4-x)+9=1+4(x-1) | | x-1+x=-9 | | 2x+6x+8=6x+4 | | 5x-6+3x=-6 | | 5-t-3=-1+2(t-3) | | 4x+7=-8x-29 | | 4g-4=40 |

Equations solver categories